The objective of “the divorced woman box” to insure the execution of the expenses towards the divorced woman and her children – A study in law 15-01 - Derradji, Kamel; Mahrouk, Karima (Journal of Human Sciences, 2021)
Expenses in favour of the divorced woman via justice (and her children) are at aim of preserving their dignity. In spite of the fact that law punishes who doesn’t pay these expenses remain insufficient that’s why Algerian law has created (the divorced woman box) according to 15-01 law to insure the execution of law verdict, as far as expenses are concerned. In other words (the divorced woman box) pays these expenses so as to take them later from the ex-husband (the father) as law dictates using lawful means.